CHLORAMBUCIL PLUS RITUXIMAB AS FRONT-LINE THERAPY IN ELDERLY/UNFIT PATIENTS AFFECTED BY B-CELL CHRONIC LYMPHOCYTIC LEUKEMIA: RESULTS OF A SINGLE-CENTRE EXPERIENCE. - Luca Laurenti; Barbara Vannata; Idanna Innocenti; Francesco Autore; Francesco Santini; Nicola Piccirillo; Tommaso Za; Silvia Bellesi; Sara Marietti; Simona Sica; Dimitar G. Efremov; Giuseppe Leone (Mediterranean Journal of Hematology and Infectious Diseases)
Currently standard first line therapy for fit patients with B-CLL/SLL are fludarabine-based regimens. Elderly patients or patients with comorbidities poorly tolerate purine analogue-based chemotherapy and they are often treated with Chlorambucil (Chl). However, complete response (CR) and overall response (OR) rates with Chl are relatively low. We now investigated whether the addition of Rituximab to Chl will improve the efficacy without impairing the tolerability in elderly and unfit patients. We included in our study 27 elderly or unfit patients that had not received prior therapy. All patients were treated with Chl (1mg/Kg per 28-day cycle for 8 cycles) plus Rituximab (375 mg/m2 for the first course and 500 mg/m2 for subsequent cycles until the 6th cycle). We obtained an OR rate of 74%. The most frequent adverse effect was grade 3-4 neutropenia, which occurred in 18.5% of the patients. Infections or grade 3-4 extra-hematological side effects were not recorded. None of the patients required reduction of dose, delay of therapy or hospitalization. Overall, these data suggest that Chl-R is an effective and well tolerated regimen in elderly/unfit patients with CLL.